Temporal trends and epidemiological impact of metabolic risk factors on stroke burden in Chinese individuals aged 65 and older, 1992–2021 - Wang, Haiying; Wang, Xiaofeng; Wang, Jia; Geng, Lin; Hou, Shaohua; Li, Pu; Wang, Qiang; Cui, Yali; Sun, Shengli (Frontiers in Neurology, 2025)
BackgroundStroke remains a principal cause of mortality and disability globally, with approximately 75 percent of strokes affecting individuals aged 65 and older. High fasting plasma glucose (HFPG), high LDL cholesterol (LDL-C), and high systolic blood pressure (SBP) are significant metabolic risk factors contributing to the increasing stroke burden. Despite this, the specific impact of these factors on stroke distribution within China, the world’s most populous aging nation, has not been extensively explored. This study investigates the influence of HFPG, LDL-C, and SBP on the stroke burden among China’s elderly population from 1992 to 2021.MethodsUtilizing data from the Global Burden of Disease (GBD) 2021 database, this study assesses the trends in stroke burden attributable to metabolic risks among Chinese individuals aged 65 years and older from 1992 to 2021. Joinpoint regression analysis was employed to identify changes in age-standardized deaths rate (ASDR), while age-period-cohort (APC) analysis helped delineate the roles of age, period, and cohort effects on stroke mortality. Future projections up to 2031 were estimated using autoregressive integrated moving average (ARIMA) models.ResultsThe study period saw a decline in age-standardized rates (ASRs) of stroke-related mortality and disability-adjusted life years (DALYs) across all metabolic risk factors, indicating progress in healthcare and public health efforts. Despite these improvements, the absolute numbers of deaths and DALYs continued to rise, propelled by an aging population and increasing prevalence of metabolic disorders. High SBP [1,241,130 (95% UI: 785,358–1,711,112)] was identified as the most significant contributor to stroke-related mortality among the elderly in China, followed by HFPG [243,757 (95% UI: 175,821–324,600)] and LDL-C [249,106 (95% UI: 70,548–449,517)]. Projections suggest that while ASDR may decrease, the absolute number of stroke-related deaths linked to these metabolic risks will continue to increase through 2031.ConclusionDeveloping effective population-specific strategies targeting high SBP, HFPG, and LDL-C is crucial for substantially reducing the stroke burden among China’s elderly. Given the significant population-attributable fractions of these risk factors, it is vital for China to rigorously evaluate its disease burden and implement targeted prevention and control strategies to mitigate future impacts.